PERBANDINGAN RISIKO CA SERVIKS BERDASARKAN PERSONAL HYGIENE PADA WANITA USIA SUBUR DI YAYASAN KANKER WISNUWARDHANA SURABAYA - Nessia Rachma Dianti; M. Atoillah Isfandiari (Universitas Airlangga, 2016)
About 500.000 cervical carcinoma new cases are found with more than 250.000 deathcases annually (Rasjidi, 2009). Cervical cancer is the highest prevalence of disease among women inIndonesia, it is equal to 0,80/00 (Kemenkes RI, 2015). Cervical cancer is caused by multifactors which areable to increase cervical cancer case, one of risk factors is personal hygiene. This study aims to analyzecervival cancer risk diff erence based on personal hygiene which consists of vaginal antiseptic usage,frequency of changing underpants, frequency of changing napkins, water utilization for vagina, publictoilet utilization, vaginal discharge history, joint towel and underpants among childbearing women. Thisstudy is a case control study which case groups are 15–49 old women with cervical carcinoma, whilecontrol groups are 15–49 years old women and are undiagnosed cervical cancer. The result of this studyshowed that joint underpants has the highest Risk Diff erence (RD = 51.42%; 95% CI: 1.73-57.48). It isrecommended for women to keep personal hygiene.Keyword: personal Hygiene, Cervical Cancer, Cervical Cancer risk